Understanding spatial heterogeneity in GB agricultural land-use for improved policy targeting - Patrick W. Saart; Namhyun Kim; Ian Bateman (Cardiff University, Cardiff Business School, 2021)
Today, one of the biggest challenges facing the UK is the new target set when the nation became first major economy to pass net zero emissions law, which requires the country to bring all greenhouse gas emissions to net zero by 2050. On the one hand, there are already a few ideas about how we should farm and use land in order to deliver such a target. On the other hand, the government has a new strategy which is to pay farmers for providing public goods, especially for climate change mitigation through the reduction and storage of greenhouse gas emissions. The most critical task is to find a solution to such a question as "How should public spending on farm public goods be allocated?" In this paper, we argue that formulating an effective subsidy scheme cannot focus on the public need alone, but should also take into consideration what farmers must endure and the opportunities they must forgo. This requires a good understanding about the generating process behind the spatial heterogeneity of agricultural land-use at a _ne spatial scale. We aim to provide government and its agents with decision support for policy making post-Brexit in two directions. Firstly, we employ detailed spatial resolution data and establish a new statistical tool that can help: (i) to effectively capture the spatial heterogeneity of agricultural land-use, (ii) to disentangle the contributions of terrain formulations, environmental characteristics, climatic conditions, policies, and other legacy and agglomeration effects in the generating process of the land-use patterns, and (iii) accurately gauge their relative importance across different regions of GB for more targeted subsidies schemes. Secondly, we employ our new method and provide policy advice and evaluation.
Keywords: C13; C21; C23; C34; Q15; Q53; 330; Agro-environmental policy; land-use; multivariate Tobit; system of censored equation; spatial model; error component model